Influence of Business Networking on Competitiveness of Small and Medium Agro Processing Firms in Murang’a County, Kenya - Kinyanjui, Muranga Bedan; Kabare, Karanja; Waititu, Anthony (Archives of Business Research, 2018)
The purpose of this study was to analyze the influence of business networking on competitiveness of small and medium agro-processing firms in Murang’a County, Kenya. Most farmers and agro processors in Kenya export semi-processed, low-value produce, some of which they later import as finished products. In order to earn more from their efforts, agro-processors in Kenya must embark on production of consumer ready products that will compete regionally and globally. To attain this competitiveness, the agro-processors must strategically engage in business networks that will greatly influence their competitive success. The choice of the rural county of Murang’a in Kenya was informed by the assumption that the findings of the study can be generalized to suit all the other rural counties of Kenya. Porter’s diamond theory of competitiveness guided the study but three other relevant theories were also considered. The study adopted correlation research design to guide the collection, analysis and presentation of data. Questionnaires were the main instruments of collecting data from respondents sampled from 180 agro-processing firms in Murang’a County. Quantitative data was analyzed using SPSS while the qualitative data was subjected to content analysis. The study established that business networking significantly influences the competitiveness of small and medium agro-processing firms in Murang’a County, Kenya since it aided the agro processing firms to improve their brands’ value, productivity and profitability. However, the networks that agro processing firms in Murang’a County engaged in were based on trust and not formally established.